Marketing Promotion Strategy Planning "Café Pondok Miso Khas Riau" Through Instagram - Feriadi, Felix (Ilomata International Journal of Management, 2024)
This study examines the promotional strategy planning for Café Pondok Miso Khas Riau through Instagram, aiming to boost consumer awareness. The topic is interesting due to the café's unique offering of traditional Miso from Riau, Indonesia, and the growing importance of social media in modern marketing. The primary problem addressed is the café's lack of brand recognition and ineffective use of social media for promotion, leading to the research question: How can Instagram be utilized to enhance the café's marketing strategy? The novelty lies in focusing on Instagram as the primary promotional tool, an approach not extensively explored for this café type. The research utilizes the SOSTAC model, involving a thorough situation analysis, setting specific objectives, and formulating strategic tactics to boost the café's online presence. Empirical findings suggest that a well-structured Instagram campaign can significantly enhance brand visibility and customer interaction. The conclusion suggests that implementing this strategy can enhance brand awareness and attract more customers, providing a valuable framework for other businesses seeking to optimize their social media marketing efforts.